Assistance in the Implementation of Social Media and Google Maps to support Ecotourism Potential in Teratak Village - Firmansyah, Firmansyah; Pratama, Yusuf Hendra; Wibisana, Bayu; Azhari, Elfan; Fitrianingsih, Baiq (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Ecotourism potential in various regions has become the main focus in the development of sustainable tourism. Teratak Village, as a potential ecotourism destination, faces challenges in utilizing digital technology to expand its reach. This community service aims to assist Teratak Village in implementing social media and Google Maps as tools to improve the promotion and management of ecotourism destinations. The service approach is carried out using a qualitative method through in-depth interviews with local stakeholders and the local community. The results of the dedication show that the application of social media, such as Instagram, Facebook, and Tiktok, has helped increase the exposure of Teratak Village to a wider audience. Google Maps plays an important role in providing accurate and easily accessible navigation guides for tourists who want to visit Teratak Village. However, several obstacles were found such as limited internet access in several areas of the village, lack of understanding of the potential of social media among some local stakeholders, and the need for more effective management in maintaining actual content on these platforms. For further dedication, suggesting the need for training for local communities in using social media effectively to promote ecotourism, as well as the important role of tourism managers in managing and maintaining precise and accurate information on digital platforms.